Jamaica and Brianna - Havill, Juanita; O'Brien, Anne Sibley (Boston : Houghton Mifflin, 1993)
Jamaica hates wearing hand-me-down boots when her friend Brianna has pink fuzzy ones.
Elem. School Library Collection, June 2000
2.4
K-3
470L
K
Center for the Collaborative Classroom Curriculum.
Keywords: Jealousy -- Fiction; Boots -- Fiction; Friendship -- Fiction